Systemic lupus erythematosus Association between Osteomyelitis: A two-sample Mendelian randomization study in European population - Minhua Hu; Zhizhong Sun; Xintao Tang; Wenxing Zeng; Hongsong Yan; Ziwei Jiang; Feng Huang (Heliyon, 2023)
Background: Systemic lupus erythematosus (SLE) has been correlated with osteomyelitis (OM), yet the underlying causal relationship remains poorly understood. This study aims to investigate the causal association between SLE and OM using Mendelian randomization (MR) analysis. Methods: Genetic instrumental variables (IVs) correlated with SLE were extracted from a comprehensive genome-wide association study (GWAS) summary database (5201 cases and 9066 controls). OM was considered a SLE phenotype, and summary data from the fast GWA data portal were utilized for the analysis. Eligible IVs were extracted following rigorous quality control measures (P < 5 × 10-8, LD r2>0.001, distance 1 Mb, and F > 10). MR analysis was conducted using the Inverse Variance Weighted (IVW), MR-Egger, and Weighted Median (WM) methods after excluding potential confounders. Cochran's Q was applied for heterogeneity test. Pleiotropy was evaluated through MR-Egger intercept, MR-Pleiotropy Residual Sum and Outlier (MR-PRESSO) method, and Leave-one-SNP-out analysis. Result: A total of 40 eligible IVs were included for MR analysis. IVW results demonstrated a positive causal association between SLE and OM (P = 0.049, OR = 1.167). Heterogeneity analysis reveal no significant heterogeneity in the IVW analysis (P = 0.5503). Pleiotropy tests, including MR-PRESSO global test and MR-Egger intercept, indicated no evidence of pleiotropy in our findings (P > 0.05). Additionally, the Leave-one-SNP-out analysis showed no substantial deviations when removing individual SNPs, thus supporting the robustness of our results. Conclusion: This study establishes a genetic causal relationship between SLE and OM, indicating an increased risk of developing OM in individuals with SLE. Therefore, proactive management of SLE is advised to mitigate the risk of developing OM.